Troublesome women: gender, crime and punishment in antebellum Pennsylvania - Hayden, Erica Rhodes (The Pennsylvania State University Press, 2019)
"Examines the lived experiences of women criminals in Pennsylvania from 1820 to 1860, mainly as they navigated the nineteenth-century legal and prison systems"--Provided by publisher